Creative industry of cities and regions: main features - Abasova, A.; Mamedova, K.; Абасова, А. А.; Мамедова, К. М. (Харківський національний автомобільно-дорожній університет, 2023)
The article focuses on the importance of the developing creative industries in cities and regions as impulses for increasing the economic potential of territories and expanding the range of goods and services produced within territories. They could also be of tremendous importance working as translators of the territory’s local identity to the global world. Analysis of recent research and publications underscores the creative sector's importance as a critical growth factor and a magnet for intellectual, creative personnel in the global arena. Theoretical and methodological foundations of the creative economy, popularized in recent decades, continue to be promising scientific developments in the search for progressive drivers of economic growth. Unresolved components within the creative industry demand meticulous examination, outlining primary challenges that persist and merit further exploration. The objectives of the article are to illuminate the pivotal role of creative industries in urban and regional development, emphasizing their contribution to economic, social, and cultural dynamics. The study explores stimulating conditions and production factors propelling the development of creative spheres, contributing to the ongoing discourse on progressive drivers of economic development in the contemporary world. Beyond economic parameters, the paper elucidates the profound intellectual and cultural implications of the creative industry. It serves as a reservoir for generating new knowledge, ideas, and technologies, preserving cultural heritage, promoting intercultural interaction, and transferring knowledge to subsequent generations. The main material of the research emphasizes the role of creative spheres as a special human activity meeting modern requirements for progressive development. The creative industry, as a branch of the economy, is based on the development of ideas, human intellectual activity, and technologies. It is concluded that the main feature of creative industries is the presence of a source of individual creativity, skills and talent with the potential to create jobs and well–being through the production and exploitation of intellectual property. A number of positive effects of developing creative industries (economic, social, cultural, innovative) are highlighted, allowing flexible integration into the new economic reality and contributing to the implementation of mechanisms for generating the creative potential of cities and regions. The development of creative industries ensures the disclosure of creative, intellectual, and innovative potential, adapting to deep and dynamic changes.
Креативна індустрія міст і регіонів: основні риси
Keywords: creative industries; intelligence; creativity; innovation; regional economy; digital economy; креативні індустрії; інтелект; творчість; інновації; регіональна економіка; цифрова економіка; 338.45:332.024; 10.30977/ЕТК.2225-2304.2023.42.134